More HIV-1 RNA detected and quantified with the Cobas 6800 system in patients on antiretroviral therapy. (31st May 2022) - Wirden, Marc; Palich, Romain; Abdi, Basma; Valantin, Marc Antoine; Tubiana, Roland; Schneider, Luminita; Seang, Sophie; Faycal, Antoine; Sellem, Baptiste; Katlama, Christine; Calvez, Vincent; Marcelin, Anne Geneviève
Abstract: Background: Target-detected (TD) results or low-level viraemia (LLV) can be observed in HIV-1 patients on ART, which regularly raises questions. Objectives: We describe here the impact on HIV-1 RNA quantification of switching from the COBAS AmpliPrep/COBAS TaqMan (CAP/CTM) to the Cobas 6800 system (C6800), based on analyses of viraemia close to the lower limit of quantification (LLoQ). Patients and methods: We retrospectively selected two groups of patients: 200 individuals whose viral loads (VLs) were consistently <50 copies/mL with CAP/CTM for at least 3 years before switching to C6800 (group 1), and 35 other patients with confirmed LLV when C6800 was in use (group 2). In both groups, we compared several consecutive VL results performed before and after the change of quantification assay. Analyses were performed with McNemar's paired tests or Fisher's exact tests. Results: In group 1, the frequency of TD results (below or above the LLoQ) increased significantly after the switch to C6800 for patients with <25% of results being TD for VLs performed with CAP/CTM ( P  < 0.0001). Significantly more patients had at least one VL ≥20 or ≥50 copies/mL with C6800, in both group 1 (37.0% versus 18.5%; P  < 0.0001 and 6.5% versus 0%; P =  0.0009, respectively) and group 2 (100% versus 66%; P  = 0.0015 and 97% versus 40%; P  < 0.0001, respectively). Conclusions: C6800 revealed residual or low-level HIV-1 RNA that was not detected with CAP/CTM, resulting in twice as many patients being found to have a VL ≥20 copies/mL. Physicians and patients should be aware of possible differences in results between assays, and it is crucial to specify the quantitative assay used in studies.